2016
DOI: 10.1002/cncr.29739
|View full text |Cite
|
Sign up to set email alerts
|

Use and effectiveness of quitlines versus Web‐based tobacco cessation interventions among 4 state tobacco control programs

Abstract: BACKGROUND:Comparative effectiveness studies of state tobacco quitlines and Web-based tobacco cessation interventions are limited. In 2009, the US Centers for Disease Control and Prevention undertook a study of the comparative effectiveness of state quitlines and Web-based tobacco cessation interventions. METHODS: Standardized questionnaires were administered to smokers who enrolled exclusively in either quitlines or Web-based tobacco cessation services in 4 states in 2011-2012. The primary outcome was the 30-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…21 Two studies that have examined the association between race/ethnicity and selection of web-only tobacco quitline service found that, compared with non-Hispanic Whites, African Americans were less likely to choose a web-only option. 22,23 Selection of the web-only program was also lower among enrollees with low education levels, who were unemployed, older, American Indians/Alaska Natives, and those who self-identified as bi/multi-racial. 23 However, differences in the selection of web-only vs telephone counseling were likely underestimated due to the underrepresentation of African Americans and other racial/ethnic minority groups, and study attrition.…”
Section: Tobacco Cessation Interventions and Digital Inequality -Webbmentioning
confidence: 99%
“…21 Two studies that have examined the association between race/ethnicity and selection of web-only tobacco quitline service found that, compared with non-Hispanic Whites, African Americans were less likely to choose a web-only option. 22,23 Selection of the web-only program was also lower among enrollees with low education levels, who were unemployed, older, American Indians/Alaska Natives, and those who self-identified as bi/multi-racial. 23 However, differences in the selection of web-only vs telephone counseling were likely underestimated due to the underrepresentation of African Americans and other racial/ethnic minority groups, and study attrition.…”
Section: Tobacco Cessation Interventions and Digital Inequality -Webbmentioning
confidence: 99%
“…The methodology primarily used was to calculate cost of service per person quit, per quit attempt or per service user. In several studies, quitlines achieved significantly higher abstinence rates than online services (An et al, 2010;Neri et al, 2016). Despite this, when cost effectiveness indicators were included in outcome evaluations, online services show a considerable comparative advantage in achieving far lower cost per quit rate (Graham et al, 2013).…”
Section: Part 3: What Measures and Methods Are Used For Evaluating Onmentioning
confidence: 99%
“…Others viewed the campaigns in a more positive way, arguing that in spite of the effectiveness in the aspect to reduce the smoking rate, the anti-smoking initiatives had produced short-term positive outcomes. For examples, the development of awareness of health risks, motivation and intention to quit smoking, smoke less number of cigarettes per day (Brennan et al, 2011;Moodie et al, 2014;Neri et al, 2016;Tyrrell, 1998;Wakefield et al, 2015;White et al, 2003). Nevertheless, the effectiveness of the anti smoking initiatives turn out to be far less encouraging, with significant evidence that the number of smokers in Australia has increased from 21,000 to 2.4 million for the ever first time despite the rigorous implementation of anti-smoking initiatives since 2013 (Adam, 2017;Colin, 2018).…”
Section: Effectiveness Of Anti-smoking Initiatives In Australiamentioning
confidence: 99%